Health aspects of active bodybuilders: monitoring by multidisciplinary team - Bruno Coraucci-Neto; Rodrigo Fenner Bertani; Giulliard Oliveira Campos; José Maria Thiago Bonardi; Nereida Kilza da Costa Lima (Colégio Brasileiro de Ciências do Esporte, 2021)
ABSTRACT Preparation in bodybuilding involves high-intensity workouts and drastic feeding strategies. Little is known about health risks. Athletes (n=510, 59.8% male) were evaluated about health aspects, anthropometry, and blood pressure (BP). Chronic diseases were reported by 6,6%, but 88.9% of them did not treat; 1.9% reported hypertension, with 15.7% having high BP; and 52.5% reported the use of prohibited drugs in the last 6 months. Body mass index was 26.2±2.5 for man and 22.3±2.2 Kg/m2 for woman. Men had lower monitoring than women by physical education professionals, nutritionists, and physicians (p<0.01). Athletes are exposed to health risks factors such as lack of knowledge about diseases, high use of prohibited substances and less monitoring by professionals among men.